2024
DOI: 10.3389/fmed.2024.1322440
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination willingness among people living with HIV in Shijiazhuang, China: a cross-sectional survey

Xihong Zhang,
Haoting Zhan,
Lijing Wang
et al.

Abstract: ObjectivesThe COVID-19 pandemic imposed an enormous disease and economic burden worldwide. SARS-CoV-2 vaccination is essential to containing the pandemic. People living with HIV (PLWH) may be more vulnerable to severe COVID-19 outcomes; thus, understanding their vaccination willingness and influencing factors is helpful in developing targeted vaccination strategies.MethodsA cross-sectional study was conducted between 15 June and 30 August 2022 in Shijiazhuang, China. Variables included socio-demographic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…Moreover, the multivariate logistic regression analyses showed that individuals who believed in the usefulness and safety of vaccinations were 1.7 and 2 times more willing to be vaccinated than those who had a negative attitude. These findings are consistent with those of previous studies conducted in different populations establishing that having positive opinions regarding vaccinations generally has a significant impact on their acceptance [ 37 , 38 ]. Therefore, public health education campaigns tailored to patients exhibiting skepticism towards the effectiveness and safety of vaccinations could lead to a significant increase in vaccine acceptance and uptake.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the multivariate logistic regression analyses showed that individuals who believed in the usefulness and safety of vaccinations were 1.7 and 2 times more willing to be vaccinated than those who had a negative attitude. These findings are consistent with those of previous studies conducted in different populations establishing that having positive opinions regarding vaccinations generally has a significant impact on their acceptance [ 37 , 38 ]. Therefore, public health education campaigns tailored to patients exhibiting skepticism towards the effectiveness and safety of vaccinations could lead to a significant increase in vaccine acceptance and uptake.…”
Section: Discussionsupporting
confidence: 93%